Nanotechnology for Electronic Materials and Devices - Korkin, Anatoli.; Korkin, Anatoli.; Gusev, Evgeni.; Gusev, Evgeni.; Labanowski, Jan K.; Labanowski, Jan K.; Luryi, Serge.; Luryi, Serge. (Nanostructure Science and Technology,, 2007)
This book is designed as an introduction for graduate students, engineers, and researchers who want to understand the current status and future trends of micro- and nano-electronic materials and devices. It also serves as an essential reference for nanotechnology "gurus" who need to keep abreast of the latest directions and challenges in microelectronic technology. Written by leading experts in each research area the viewpoints presented can help to foster further research and cross-disciplinary interactions required to surmount the barriers facing future generations of technology design. .